SDS-PAGE Analysis of Protein Characteristics in Developing Fruit of Lagenaria leucantha - LI Ying; YU Jing-quan; ZHU Zhu-jun (浙江大学学报. 农业与生命科学版)
In seed plants, successful fruit set and subsequent development are dependent on pollination and fertilization since fertilization activates cell division and triggers fruit development by producing phytohoimones especially auxins and GAs. Fruit set was very low in Lagenaria leucantha Rusby during early spring. We found that CPPU［N-(chloro-4-pyridyl)-N′-phenyurea］, a new kind of cytokinin, was more effective than NAA and GA3 in inducing parthenocarpic fruit growth and in decreasing fruit abortion. In this paper, we examined the possible role of fertilization and CPPU in protein synthesis in developing fruit of Lagenaria leucantha by SDS-PAGE analysis.